Avaliação de um método para estimar a absorção radicular do nitrato em arroz - Blanger, Bruna Regina (2021)
Plant roots absorb nitrogen in the form of nitrate (NO3 - ) and ammonium (NH4 + ). Among the studies of evaluating the kinetics of nitrogen absorption in rice and other species, the most used method is the evaluation of the reduction in its concentration in the nutrient solution over time. However, this method presents complications of a physiological nature, statistical nature, and another error, which is because of the procedural nature. From a physiological point of view, the complication is at the root. Nitrogen transporters are subject not only to treatment, but to all the different concentrations of this element, which can affect its affinity and consequently its operation. In statistical terms, the successive evaluations in the same experimental unit lead to the autocorrelation of the residuals, which contradicts their independence required to enable the adjustment of regression models. The procedural error that is made, and in most cases it is not explicit, occurs when the volume of sample extracted from the solution with chemically pure water is not replaced. Considering these aspects, and noting that there are no reports in the literature about other alternative methods in the same line of evaluation, it is proposed to evaluate a method of kinetics of nitrate uptake in rice based on plant exposure to only one single ion concentration treatment, evaluating its content in the root system after a certain period of exposure time. This solution would avoid all the problems already mentioned. To determine the NO3 - contents, a case study was carried out using the Kjeldahl method. The method proposed in this paper did not produce satisfactory results, specifically due to the limitation of the Kjeldahl method, whose resolution (detection limit) makes it impossible to identify magnitude values of those found in the absorption kinetics of nitrate in rice. As a suggestion, the proposed method needs to be revalidated using another method of detecting the total N content or specifically NO3 - in the roots of these plants, but with the required resolution.